10 Questions and 4 experts on Corona: Answers by Akiko Iwasaki, Gérard Krause, Samuel Alizon, and Rino Rappuoli. Issue 5 (24th April 2020) - Carret, Celine K
Abstract : A multi‐person interview on the unrolling corona pandemic with Samuel Alizon, Akiko Iwasaki, Gerard Krause and Rino Rappuoli.